Structural damage assessment of Huaca de la Luna, Peru: Preliminary results from ongoing multidisciplinary study - Aguilar, R (2016)
This paper presents a comprehensive update of the structural damage assessment of the complex Huaca de la Luna, which is one the most important heritage monuments in northern Peru, and was built by the Moche civilization from 100 AD to 650 AD. The paper presents an overview of the initial hypothesis identified to explain the nature of the damage encountered in the Huaca. The results highlight how the combination of material evaluations, coupled with geotechnical investigations have been essential in constructing a series of 2D nonlinear FE models for the structural analyses under gravitational loading of the Huaca. Results of the analyses conducted to date show the importance of a multidisciplinary approach for assessing the structural safety in these types of buildings. © 2016 Taylor & Francis Group, London.